Identifying the optimum source of mesenchymal stem cells for use in knee surgery. Issue 9 (2nd March 2017) - Davies, Benjamin M.; Snelling, Sarah J.B.; Quek, Lynn; Hakimi, Osnat; Ye, Hua; Carr, Andrew; Price, Andrew J.
ABSTRACT: Single sitting procedures where the mononuclear cell fraction is extracted from bone marrow and implanted directly into cartilage and bone defects are becoming more popular as novel treatments for cartilage defects which have, until now had few treatment options. This is on the basis that the mesenchymal stem cells (MSCs) contained within will repair the damaged tissue. This study sought to determine if the femur and tibia could provide equivalent amounts of mesenchymal stem cells, with equivalent viability and proliferative capacity, to that obtained from the gold standard of the pelvis in order to potentially reduce the morbidity associated with these procedures. Bone marrow was extracted from the pelvis, femur, and tibia of human subjects. The mononuclear cell fraction was extracted and cultured in the laboratory. Mesenchymal stem cell populations were assessed using a colony forming unit count. Viability was assessed using a PrestoBlue viability assay. Population doubling number was calculated between the end of passage 0 and passage three to determine the proliferative abilities of the different populations. Finally, the cell surface phenotype of the cells was determined by flow cytometry. The results showed that the pelvis was superior to the femur and tibia in terms of the number of stem cells isolated. There was no statistically significant difference in the phenotype of the cells isolated from different locations. This work shows that when undertaking single sitting procedures, the pelvis remains the optimum source for obtaining MSCs, despite the morbidity associated with bone marrow collection from the pelvis. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1868–1875, 2017.